Missed Opportunities to Diagnose Common Variable Immunodeficiency: a Population-Based Case–Control Study Identifying Indicator Diseases for Common Variable Immunodeficiency - Dahl, Christina; Petersen, Inge; Ilkjær, Frederik V.; Westh, Lena; Katzenstein, Terese L.; Hansen, Ann-Brit E.; Nielsen, Thyge L.; Larsen, Carsten S.; Johansen, Isik S.; Rasmussen, Line D. (Journal of clinical immunology, 2023)
Purpose Delayed diagnosis of common variable immunodeficiency (CVID) remains a serious problem. We investigated whether some diseases diagnosed during out-patient visits or admission to hospitals could act as indicator conditions for CVID diagnosis. Methods In this nested case–control study, we identified 128 cases diagnosed with CVID in Denmark (1999–2013) and 640 age-, gender-, and region-matched controls. We obtained data on diseases diagnosed at hospitals in the five years before CVID diagnosis from The National Hospital Registry. We grouped hospital diagnoses in 33 major disease categories and 210 subcategories. We used conditional logistic regression to calculate the odds ratios (OR) and 95% confidence intervals (CI) to estimate associations between disease exposure and subsequent CVID. Results During the five years preceding a CVID diagnosis, cases had four times as many hospital contacts as the controls ( p < 0.001). A diagnosis in 18 major disease categories showed a significant OR for subsequent diagnosis of CVID. The most substantial association with a subsequent CVID diagnosis was a diagnosis of lower respiratory tract infections (OR: 29.9; 95% CI: 14.2–63.2) and lung diseases (35.1; 15.0–82.5). We observed a similar association when we removed the last year before diagnosis from analysis and overall, in the years < 1, ≥ 1–3, and ≥ 3–5 before diagnosis, although the absolute number of exposures was small. Twenty-eight specific diseases displayed an at least 3-fold risk of subsequent CVID diagnosis. Conclusion Targeted screening for antibody deficiency in patients diagnosed with specific diseases associated with CVID may lead to earlier CVID diagnosis and treatment and thereby potentially reduced morbidity and mortality.